Factors That Cause Insecurity in College Students When Viewing Tiktok Content - Rahmayanty, Dinny; Lubis, Muhammad Alridho; Mahardika, Rani; Pitria, Pitria; Mulyani, Melati Rizki; Lizia, Aisyah; Sadewa, Raja Dhimas (Faculty of Education Universitas Negeri Malang, 2024)
Social media is an online platform that enables interaction, content sharing and collaboration between users. TikTok is one example of a popular social media platform, particularly in the creation and sharing of short videos. The use of TikTok has both positive and negative impacts on its users. One of the negative impacts of using Tik Tok is the emergence of feelings of insecurity that affect the mental well- being of its users. This study aims to understand the factors that lead to increased feelings of insecurity in university students when they interact with TikTok content. The research method used is qualitative research with a literature review approach. The results showed that insecure feelings can be triggered by failure, social anxiety, perfectionism, and self-comparison with others, especially on social media. It is important to manage these feelings well and develop strategies to improve self-esteem and mental resilience. By understanding the factors that influence feelings of insecurity, we can identify effective intervention strategies to reduce their negative impact and promote college students' mental and emotional well-being. This research highlights the urgency and relevance of understanding the factors that cause insecurity in university students when viewing Tik Tok content. Topics covered include social media, TikTok, content, insecure, factors that cause insecurity by TikTok content, and efforts to overcome insecure feelings in college students